Bodies, Landscapes, and the Air That We Breathe - Frizell, Caroline (Archīum Ateneo, 2024)
This article maps out material-discursive entanglements of bodies and landscapes, speaking from bodies-in-movement as ecokinetic poetic phenomena. The first-hand experience of waiting on the end of a phone line for information on disability support becomes a springboard to unpack the term material-discursive, locating it in posthuman thinking, with a focus on the way normative discourses become inscribed at an embodied level. When COVID-19 arrived, or perhaps erupted from within, bodies turned into sites of suspicion and precarity, mirroring the oppressive clout of normative discourses, that move invisibly and insidiously, creating and being created by relations of power. Hands, face, and space became a focus of attention: Don’t touch. Cover your nose and mouth. Keep your distance. The Other carries potential contamination. Zones of human relations are exposed as zones of exclusion(s). During the COVID-19 pandemic,, there grew a stark realisation that the self is a phenomenon implicated within a relational matrix in which we are only OK, if we are all OK. Macro, mezzo, and micro matters connect at every manoeuvre as we navigate personal, political, and cultural landscapes. Each breath is a reminder: I am matter connected to all that is pumped into the air, from salty breezes from the Atlantic, to oxygen gifted by the eucalyptus, to polluted layers of city smog. What we do to the air, we breathe back in. What we do to the earth, we do to ourselves. This writing seeks to identify how an understanding of bodies-in-movement as ecokinetic poetic phenomena can promote empathic and compassionate sociocultural and political relationships towards creating cultures of care.